Strategies to Increase Income of Small and Medium Micro Enterprises Traders (Small Stalls) to Meet Family Needs (Case Study in Passo Village, Baguala District, Ambon City) - Mirel Sampe; Melianus Salakory; Edward Gland Tetelepta (Jurnal Pendidikan Geografi Unpatti, 2024)
Small cottage traders is a term used to refer to traders who run businesses in simple or small places and economic businesses who now have businesses that are often managed independently and also have limited capital but provide easy access for consumers. The purpose of this research aims to influence the length of business, monthly income level and the influence of time in sales for small kiosk traders. The type of research used is descriptive which is used to solve existing problems using SWOT analysis to determine Strengths and Weaknesses. ), Opportunity (opportunity) and threat (Threat). The results of this research show that the income level of small kiosk traders in Passo Village can meet economic needs such as education, clothing, food and shelter and health with a percentage of 100%, so that in general all economic needs are very well met.